Penguatan Identitas Melalui Branding Kemasan dan Diversifikasi Produk Usaha Comel - Ni Nyoman Wulan Antari; Riza Wulandari (Studi Kasus Inovasi Ekonomi, 2019)
Currently a variety of strategies are strived by the entrepreneurs to strengthen their identity efforts amid new products popping up by presenting renewability in accordance with the interest that exists in the market. Partners in public service activities this is Kiki Adelya a young entrepreneur trying to do creative food products namely remahan beans and gnetum Brown named "Winsome". Partners often obtain orders for the event, wedding, and anniversary poems for personal consumption. Location of partners located in Banjar new temples, Gianyar. Currently owned by business partners are experiencing barriers in product development. The results of the solution that has been given is on product diversification done socializing by delivering the material results of scientific researchers on product diversification. Knowledge of product diversification which are much sought after on the market such as Yam, plantain, potato, maize and others. After the partners learned of the activities further granting of gifts in the form of additional flavor chocolate such as green tea, strawberry, white chocolate/vanilla as well as base material in addition to using a variant form of addition done Rau peanuts. Supplies product diversification has been given also practiced together with the team and partners so as to produce a new variant. The results of the second form of the creation of a more attractive packaging design to reinforce branding partners and granting standing pouch type ecobag as the site of the new packaging.